2015
DOI: 10.1051/0004-6361/201425259
|View full text |Cite
|
Sign up to set email alerts
|

ADAM: a general method for using various data types in asteroid reconstruction

Abstract: We introduce ADAM, the All-Data Asteroid Modelling algorithm. ADAM is simple and universal since it handles all disk-resolved data types (adaptive optics or other images, interferometry, and range-Doppler radar data) in a uniform manner via the 2D Fourier transform, enabling fast convergence in model optimization. The resolved data can be combined with disk-integrated data (photometry). In the reconstruction process, the difference between each data type is only a few code lines defining the particular general… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(92 citation statements)
references
References 23 publications
(62 reference statements)
1
91
0
Order By: Relevance
“…Although main belt asteroids can only be observed at relatively small phase angles (up to 30 • at most), it has been shown that their lightcurves contain signatures of non-convex topographic features, so that these features can be successfully reproduced in the shape models (Bartczak & Dudziński, MNRAS, accepted). When modelling on lightcurves is a priori complemented by auxiliary data like adaptive optics or occultation contours in one multi-data inversion process, such non-concavities gain more support (as in models created using ADAM algorithm, Viikinkoski et al 2015;Hanuš et al 2017). However, when SAGE non-convex models based exclusively on lightcurves are a posteriori compared to multi-chord occultations, their topographic features are confirmed, as has been shown in the case of binary asteroid (90) Antiope (Bartczak et al 2014), but also in simulations and real-case studies performed recently by Bartczak & Dudziński (MNRAS, accepted).…”
Section: Lightcurve Inversion Methodsmentioning
confidence: 99%
“…Although main belt asteroids can only be observed at relatively small phase angles (up to 30 • at most), it has been shown that their lightcurves contain signatures of non-convex topographic features, so that these features can be successfully reproduced in the shape models (Bartczak & Dudziński, MNRAS, accepted). When modelling on lightcurves is a priori complemented by auxiliary data like adaptive optics or occultation contours in one multi-data inversion process, such non-concavities gain more support (as in models created using ADAM algorithm, Viikinkoski et al 2015;Hanuš et al 2017). However, when SAGE non-convex models based exclusively on lightcurves are a posteriori compared to multi-chord occultations, their topographic features are confirmed, as has been shown in the case of binary asteroid (90) Antiope (Bartczak et al 2014), but also in simulations and real-case studies performed recently by Bartczak & Dudziński (MNRAS, accepted).…”
Section: Lightcurve Inversion Methodsmentioning
confidence: 99%
“…We used the ADAM algorithm (Viikinkoski & Kaasalainen 2014;Viikinkoski et al 2015) for the shape and spin reconstruction. ADAM enables an easy combining and weighting of various data types.…”
Section: Methodsmentioning
confidence: 99%
“…We used both subdivision surfaces and octantoid parametrization for shape representations (Viikinkoski et al 2015). Based on a global parametrization by spherical harmonics, octantoids produce smooth curved surfaces, while the subdivision surfaces, together with the regularization we use, are characterized by sharper local features.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations